Festschrift zur 150-Jahr-Feier des Geodätischen Instituts (1868 - 2018) - Seitz, Kurt [Hrsg.] (Schriftenreihe des Studiengangs Geodäsie und Geoinformatik / Karlsruher Institut für Technologie, Studiengang Geodäsie und Geoinformatik, 2018)
The commemorative publication of the 150-year anniversary of the foundation of the Geodetic Institute Karlsruhe (GIK) presents the historical overview of the development of the GIK. Current research results are presented and innovations are shown.